2016
DOI: 10.1007/s12182-015-0070-5
|View full text |Cite
|
Sign up to set email alerts
|

Pore-scale investigation of residual oil displacement in surfactant–polymer flooding using nuclear magnetic resonance experiments

Abstract: Research on the Gangxi III area in the Dagang Oilfield shows that there was still a significant amount of oil remaining in oil reservoirs after many years of polymer flooding. This is a potential target for enhanced oil recovery (EOR). Surfactant-polymer (SP) flooding is an effective chemical EOR method for mobilizing residual oil and improving displacement efficiency macroscopically, but the microscopic oil displacement efficiency in pores of different sizes is unclear. Nuclear magnetic resonance (NMR) is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In EOR processes, surfactant fluids recover residual oil molecules by interfacial tension (IFT) reduction. Previous studies reported that the IFT between oil and displacing fluid must decrease to ultralow magnitudes for displacement of in situ oil from pore spaces (otherwise trapped by capillary forces) of hydrocarbon-bearing reservoir rocks. , Surfactant monomers are adsorbed onto the oil/aqueous interfaces, with the hydrophobic tail groups orienting toward the oil phase and hydrophilic heads pointing toward the aqueous phase. This results in micelle/aggregate formation, which is an important transport conduit for crude oil movement. , Mixed surfactant fluids improve the oil micellization ability of constituent surfactants by forming mixed micelles in dynamic flow systems. Incorporation of ionic + nonionic surfactants into aqueous fluids reduce the repulsive interactions among charged polar head groups and favors improved adsorption efficiencies, which in turn is responsible for improved oil extraction.…”
Section: Introductionmentioning
confidence: 99%
“…In EOR processes, surfactant fluids recover residual oil molecules by interfacial tension (IFT) reduction. Previous studies reported that the IFT between oil and displacing fluid must decrease to ultralow magnitudes for displacement of in situ oil from pore spaces (otherwise trapped by capillary forces) of hydrocarbon-bearing reservoir rocks. , Surfactant monomers are adsorbed onto the oil/aqueous interfaces, with the hydrophobic tail groups orienting toward the oil phase and hydrophilic heads pointing toward the aqueous phase. This results in micelle/aggregate formation, which is an important transport conduit for crude oil movement. , Mixed surfactant fluids improve the oil micellization ability of constituent surfactants by forming mixed micelles in dynamic flow systems. Incorporation of ionic + nonionic surfactants into aqueous fluids reduce the repulsive interactions among charged polar head groups and favors improved adsorption efficiencies, which in turn is responsible for improved oil extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 184 utilized a low-frequency NMR spectrometer (Reccore-04) to quantify the distribution of oil in rock samples from the Dagang oil field in China after waterflooding, polymer injection, and SP injection. The tests aimed to evaluate the performance of different surfactant/polymer formulations for EOR applications and revealed the contribution of every pore system (i.e., small, medium, and large) to the oil recovery.…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%
“…Combining C and T 2 spectrum, the pore-radius distribution, shown in Figure 3, is obtained. The relationship between T 2 , pore radius, and pore type is shown in Table 3 following the methods of Lai et al [36] and Liu et al [42].…”
Section: Pore Radius Distributionmentioning
confidence: 99%